2022
DOI: 10.3389/fenvs.2022.928955
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Eco-Investment on E-Waste Recycling-Evidence From EU Countries

Abstract: Waste electrical and electronic equipment is the fastest growing waste stream internationally. Due to its physical characteristics, e-waste is a suitable subject for the development of recovery, repair, and recycling policies, prolonging products’ life cycle for as long as possible, and is an objective pursued by the specific mechanisms of the circular economy. From the point of view of economic development models, e-waste management is one of the areas with significant potential for the implementation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…On the one hand, MWM focuses on reducing the environmental impact of waste, and on the other hand, it pursues the recycling and reuse of certain materials. Owing to the fact that it reduces the pressure on natural resources in some situations, such as e-waste, specialists consider it to be an urban mine for certain industrial and precious metals [74][75][76]. In addition, MWM generates business opportunities, which implies the appearance of new companies in the business ecosystem of each country, as well as new jobs [77][78][79].…”
Section: Municipal Waste and Circular Economymentioning
confidence: 99%
“…On the one hand, MWM focuses on reducing the environmental impact of waste, and on the other hand, it pursues the recycling and reuse of certain materials. Owing to the fact that it reduces the pressure on natural resources in some situations, such as e-waste, specialists consider it to be an urban mine for certain industrial and precious metals [74][75][76]. In addition, MWM generates business opportunities, which implies the appearance of new companies in the business ecosystem of each country, as well as new jobs [77][78][79].…”
Section: Municipal Waste and Circular Economymentioning
confidence: 99%
“…On the one hand, WEEE contains a large number of components that can have harmful effects on the environment and humans, and its indiscriminate handling and informal recycling can make WEEE a global public and environmental health problem [3][4][5][6] . On the other hand, due to its physical properties, WEEE is ideally suited for recycling and can bring great benefits when recycled 6,7 . This makes WEEE an attractive secondary resource and environmental pollutant at the same time 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] On the other hand, due to its physical properties, WEEE is ideally suited for recycling and can bring great benets when recycled. 6,7 This makes WEEE an attractive secondary resource and environmental pollutant at the same time. 8 Waste printed circuit boards (WPCBs), which contain a large number of high-value components and toxic substances, are a critical component of all EEE and an important target for WEEE disposal.…”
Section: Introductionmentioning
confidence: 99%
“…This study contributes a pioneering analysis in the literature by being the first to explore the influence of government ideology on e-waste recycling rates. Previous research (Boubellouta and Kusch-Brand [ 8 ], Yilmaz and Koyuncu [ 9 ], Constantinescu et al [ 10 ]) has overlooked government ideology as a factor impacting e-waste recycling, and this study addresses this gap by introducing a new determinant affecting e-waste recycling rates. As far as our knowledge extends, no empirical research has investigated the relationship between government ideology and e-waste recycling rates.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicated that, globalization and its three sub-components exert a favorable influence on the e-waste recycling rates in 30 European countries. Meanwhile, Constantinescu et al [ 10 ] examined the effect of eco-investment on e-waste recycling in 24 EU countries from 2009 to 2018 and found that eco-investment per capita had a positive impact on e-waste recycled per capita during the estimation period.…”
Section: Literature Reviewmentioning
confidence: 99%